2023
DOI: 10.1002/cctc.202201298
|View full text |Cite
|
Sign up to set email alerts
|

In situ X‐ray Absorption Spectroscopy in Homogeneous Conditions Reveals Interactions Between CO2 and a Doubly and Triply Reduced Iron(III) Porphyrin, then Leading to Catalysis

Abstract: Iron porphyrins are attractive catalysts for the electrochemical reduction of carbon dioxide (CO2), owing to their high activity and selectivity while being tunable through ligand functionalization. Iron tetraphenyl porphyrin (FeTPP) is the simplest of them, and its catalytic behavior toward CO2 has been studied for decades. Although kinetic information is available, spectroscopic signatures are lacking to describe intermediate species along the catalytic cycle. In situ UV‐Visible and X‐ray absorption near edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…These considerations are consistent with CO 2 activation and reduction by the UrFe porphyrin in its formal Fe I state. By employing X‐Ray Absorption Near Edge Spectroscopy (XANES), a recent study has provided clues that an interaction between the doubly‐reduced Fe I TPP and CO 2 is possible [46] . In another study, the formation of a formal [Fe I ‐CO 2 ] adduct has been suggested to be the rate‐determining step in the photocatalytic CO 2 ‐to‐CO conversion when UrFe is used as a catalyst, with BIH as a stronger and irreversible electron donor [28] .…”
Section: Resultsmentioning
confidence: 99%
“…These considerations are consistent with CO 2 activation and reduction by the UrFe porphyrin in its formal Fe I state. By employing X‐Ray Absorption Near Edge Spectroscopy (XANES), a recent study has provided clues that an interaction between the doubly‐reduced Fe I TPP and CO 2 is possible [46] . In another study, the formation of a formal [Fe I ‐CO 2 ] adduct has been suggested to be the rate‐determining step in the photocatalytic CO 2 ‐to‐CO conversion when UrFe is used as a catalyst, with BIH as a stronger and irreversible electron donor [28] .…”
Section: Resultsmentioning
confidence: 99%
“…The active form of the catalyst seems to be Fe(0)TPP. Recently, it was reported that the triply reduced Fe(III)TPP, formally Fe(0)TPP, forms an adduct with CO 2 and that this adduct is the active form of the catalyst [32] . Intriguingly, the UV‐vis spectrum recorded under CO 2 at a potential corresponding to catalysis (−1.72 V vs. SCE) and attributed to this adduct has the same features as the doubly reduced Fe(III)TPP, i. e. formally Fe(I)TPP.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that the triply reduced Fe(III)TPP, formally Fe(0)TPP, forms an adduct with CO 2 and that this adduct is the active form of the catalyst. [32] Intriguingly, the UV-vis spectrum recorded under CO 2 at a potential corresponding to catalysis (À 1.72 V vs. SCE) and attributed to this adduct has the same features as the doubly reduced Fe(III)TPP, i. e. formally Fe(I)TPP. In light of the present analysis, we alternatively propose that the detected species, both in UV-vis and XAS, is actually Fe(I)TPP.…”
Section: Application To Co 2 Cpe Catalyzed By Fetppmentioning
confidence: 89%
“…22 All data were normalized to the intensity of the incident beam. The spectroelectrochemical cell, described elsewhere 23 and shown in Figure S6, is composed of a 0.06 mm × 6 mm × 2 mm GC working electrode, a Pt plate CE, and a silver wire floating RE. Electrodes were carefully washed by successive sonication in acetone, absolute ethanol, and water, 5 min each.…”
Section: X-ray Absorption Spectroelectrochemicalmentioning
confidence: 99%